Ferroelectric La-doped HfO2 deposited via chemical solution on silicon for tellurium field-effect phototransistors - Jeong U.; Rho H.Y.; Cho H.; Naqi M.; Oh J.O.; Cho Y.; Pujar P.; Kim S. (My University, 2025)
Chemical solution deposition (CSD) is proven viable, low-cost technique for growing thin films of various functional materials. This technique is also employed in the growth of doped-HfO2, aimed at comprehending the effectiveness of dopants in inducing ferroelectricity in HfO2; various dopants such as Zr, Y, Al, Ce, Ba have been investigated over the years. Herein, we now aim to extend the efficacy of CSD in achieving high ferroelectric output in La-doped HfO2 (HLO) directly on silicon. CSD-HLOs exhibit a remarkable remanent polarization (2Pr) of ≈ 37 µC/cm2 and coercive field (Ec) of ∼ 3 MV/cm. These CSD-HLOs when stacked with HfO2 dielectric and tellurium (Te) p-type semiconducting channel, the resulting field effect transistors (FETs) have not only demonstrated four-fold improvement in the switching characteristics but also substitutionally reduced the leakage currents. The FETs on passivation with Al2O3 demonstrated excellent stability against applied stress and these passivated FETs presented good optical response under blue light through the photogating. © 2023 Elsevier B.V.